Model-free Control of a DC-DC Boost Converter Based on the Inductor Current Averaging - Maureira, Angel; Riffo, Sebastián; González- Castaño, Catalina; Rivera, Marco; Restrepo, Carlos (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
In this work, a new model-free predictive control (MF-PC) technique is presented for controlling dc-dc converters based on calculating the slope of each switching instant. This technique has the simplicity required for converters operating at high frequencies. The simulation results show that the proposed method is robust against parameters and model changes compared to classical predictive controls.